2012 IEEE/WIC/ACM International Conferences on Web Intelligence and Intelligent Agent Technology 2012
DOI: 10.1109/wi-iat.2012.169
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Agent Social Joint Actions via Micro and Macro Coordination Strategies

Abstract: Abstract-This paper presents a multi-agent model for large crowd simulations that addresses the need for socially plausible coordination behavior. A computational model for multi-agent coordination informed by well-established common ground theory is proposed. We introduce the idea of macro-and microcoordination strategies that allow agent-based simulations to adapt to different domains. Our agent model allows the selection of appropriate behaviors based on the spatiotemporal conditions of the agent-group's en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Touch is sensed within range of character radius r, hearing can be omnidirectional with range limitation d h , and vision is directional and is effective up to a range, d v , along its body direction (for simplicity, body orientation is synonymous to gaze direction in our model) and within a field of view defined by an angle, α. Details on the situation assessment process may be found in [22]. may respond by looking at A and nodding his head in acknowledgement.…”
Section: Micro-behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Touch is sensed within range of character radius r, hearing can be omnidirectional with range limitation d h , and vision is directional and is effective up to a range, d v , along its body direction (for simplicity, body orientation is synonymous to gaze direction in our model) and within a field of view defined by an angle, α. Details on the situation assessment process may be found in [22]. may respond by looking at A and nodding his head in acknowledgement.…”
Section: Micro-behaviormentioning
confidence: 99%
“…In our previous work [22,23], we presented a group coordination model informed by Common Ground (CG) theory by Clark [5] to incorporate the impact of social interaction among group members in crowd simulations. Given that a crowd typically consists of many number of small groups and crowd dynamics emerges from the interaction of the groups [6,12], we proposed a coordination model reflecting the communication process of group members by which a cohesive movement is maintained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For pedestrian and evacuation dynamicists, they are more inclined to focus on group movement itself and its influence on the crowd movement. Usually the researchers carry out this study from three aspects: pedestrian group experiment [4,[20][21][22] local behavior of pedestrian group [4,12,20,21,[23][24][25][26] and evacuation model with the impact of the present of groups [13,14,22,[27][28][29][30][31]. These three aspects are very different approaches to investigating the phenomena in question.…”
Section: Introductionmentioning
confidence: 99%
“…In group activities, people perform actions such as body movements, gestures, and eye gazes as means of participating with others in the group, whereas crowd simulation applications that consider group organization typically focus on overall formations and inter‐member distances; Park et al . showed that communicative behavior within individual groups can impact the distribution of the simulated crowd as a whole . Applying Herbert Clark's common ground (CG) theory to model group behaviors in simulation, they demonstrated the impact of incorporation of their model on the dynamic congestion distribution in simulations but did not show that the model produced more correct or believable simulations.…”
Section: Introductionmentioning
confidence: 99%